Immunohistochemical comparison of CD5, lambda, and kappa expression in primary and recurrent buccal Mucosa-associated lymphoid tissue (MALT) lymphomas - Iino Mituyoshi; Kitabatake Kenichirou; Tanaka Toshiaki; Goto Kaoru (BMC, 2011)
Abstract Mucosa-associated lymphoid tissue (MALT) lymphoma is a type of extranodal marginal zone B-cell lymphoma and is a distinct subtype of non-Hodgkin's lymphoma. Primary MALT lymphomas can also occur in the oral cavity, although their appearance in this location is rare. The neoplastic cells of which MALT lymphomas are composed express B-cell antigens and show monotypic immunoglobulin expression with light-chain restriction. Although neoplastic MALT lymphoma cells do not express CD5, previous studies have shown that CD5 positive MALT lymphomas are more prone to dissemination than those that do not express CD5. Moreover, there are some reports that describe kappa- and lambda- dual light chain expression in B cell malignant neoplasms. A 66-year-old Japanese woman with swelling of the right buccal mucosa was referred to our hospital. The lesion was excised and was pathologically diagnosed as a MALT lymphoma tumor with a t(11;18)(q21;q21) chromosome translocation. Swelling of the right buccal mucosa recurred 2 years later. The recurrent tumor was then excised and pathologically diagnosed as MALT lymphoma. Immunohistochemical examination of CD5, lambda, and kappa expressions revealed that the primary tumor was positive for CD5, kappa, and lambda, but the recurrent tumor was weakly positive for CD5 and kappa. With respect to lambda positivity, the recurrent tumor showed negativity. Our study suggests that immunohistochemical expression of CD5, kappa, and lambda in oral MALT lymphoma have the risk of recurrence. We first described the recurrence of CD5 positive MALT lymphoma in the oral cavity and compared the immunohistochemical expressions of CD5, lambda, and kappa between the primary and recurrent tumors.